Who deserves compassion? A corpus-assisted critical discourse analysis of the discursive construction of Syrian refugees, asylum seekers, immigrants and migrants in UK newspaper reports published between October 2014 and September 2016 - Kelly, Samantha (2020)
Background: A body of research exists that investigates the representation of migrant populations in news media texts. This study extends the scope of inquiry towards the capacity for the discursive construction of social actors to shape readers’ emotional and cognitive responses of compassion. Aims: The aims of the study are to both understand how Syrian refugees, asylum seekers, immigrants and migrants (RASIM) are discursively constructed in UK newspaper reports, and establish how these representational strategies function to construct Syrian RASIM as deserving of compassion or otherwise.